Discourse Analysis at the Crossroads of Disciplines - Henry Hernández Bayter (Translation Studies: Theory and Practice, 2023)
The article serves as an introduction to the special issue of the journal touching upon discourse as an object of research with a focus on the notions of rhetoric and literature as an example of interdisciplinarity. The author provides a brief overview of the topics covered during the conference.